Correlates of preparedness for caregiving of poststroke patients: a meta-analysis - Li, Chen; Fang, Yanhui; Wang, Huan; Lin, Bingqin; Xie, Yuyao; He, Yuanyuan; Dong, Dawei; Zheng, Dongxiang (Frontiers in Neurology, 2025)
BackgroundGiven that stroke is a sudden, traumatic medical crisis and a chronic condition, identifying factors associated with caregiver preparedness is particularly important for poststroke caregivers. Therefore, we carry out this study to identify correlates of preparedness for caregiving for poststroke patients. To examine correlates of preparedness for caregiving in poststroke patients.MethodsA systematic review and meta-analysis was performed according to the PRISMA 2020 guidelines. We searched six English databases and three Chinese databases for studies published from the establishment of the database to May 2023. The quality of the evidence was assessed using the Agency for Healthcare Research and Quality scale. Statistical software R studio was used for statistical analysis.ResultsThirteen studies were included in the meta-analysis. Caregivers for poststroke patients reported relatively low-to-moderate level of caregiver preparedness. Our meta results showed that demographics characteristics of both poststroke patients and caregiver, stroke-related variables and psychological variables were associated with caregiver preparedness. And subgroup analysis stroke type contributes to heterogeneity in caregiver gender, age and relationship, caregiver type contributes to heterogeneity in caregiver experience.ConclusionThe level of caregiver preparedness ranges from low to moderate and is influenced by multiple factors. The findings may inform tailored strategies for enhancing preparedness in stroke caregivers.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42021249641.